PEMBELAJARAN BERBASIS QAEDAH BAHASA, QAEDAH TAFSIR, DAN USHUL FIQH DALAM PENDIDIKAN ISLAM - Ismasnawat; Abdul Halim Hanafi; Mursal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore and analyze Qaedah-based Learning of Language, Qaedah Tafsir, and Ushul Fiqh in Islamic Education. The problem raised is the lack of in-depth understanding of these three rules among students and teachers. The methodology used was a literature study, by collecting data from various written sources, including books, journal articles, and relevant official documents. The results showed that the Qaedah of Language serves as the linguistic basis for interpreting religious texts, the Qaedah of Tafsir provides a systematic methodology for understanding the meaning of Qur'anic verses, and Ushul Fiqh plays an important role in the development and application of Islamic law. This research is expected to make a significant contribution to the understanding and teaching of these rules in the context of Islamic education, as well as encourage the development of a more effective curriculum.